Review of General Dental Council and General Medical Council "fitness to practise" hearings related to maxillofacial surgery. Issue 6 (July 2017) - Taylor, R.; Ali, M.H.; Howe, T.E.; Varley, I.
Abstract: Dually-registered specialists in oral and maxillofacial surgery (OMFS) may be subject to disciplinary hearings by the General Medical Council (GMC) and the General Dental Council (GDC) for the same allegations, a phenomenon referred to as "double jeopardy" within the specialty. Previous efforts by both councils to simplify regulatory arrangements have made little progress. We have therefore reviewed the range and scope of fitness to practise (FTP) proceedings relevant to OMFS. We searched the online GMC register to find registered OMFS specialists and obtained FTP proceedings from 2004-2016 through a Freedom of Information request from the GDC. We then searched for cases relevant to OMFS, and cross-checked GMC and GDC registers for dual registration before reviewing relevant cases and identifying and discussing themes. Seven OMFS specialists are currently subject to GMC sanctions. A total of 22 GDC hearings related to OMFS, all of which began after 2011. Six involved the practice of OMFS, work within an OMFS department, or work by a dually-registered doctor. While "double jeopardy" is uncommon, it does happen. The cases reviewed raise issues about the remit of the GDC and their understanding of clinical practice in OMFS. We found no evidence of progress in attempts to simplify FTP proceedings. The number of GDC hearings relevant to OMFS is increasing.